Metformin is associated with reduced COVID-19 severity in patients with prediabetes. (December 2022) - Chan, Lauren E.; Casiraghi, Elena; Laraway, Bryan; Coleman, Ben; Blau, Hannah; Zaman, Adnin; Harris, Nomi L.; Wilkins, Kenneth; Antony, Blessy; Gargano, Michael; Valentini, Giorgio; Sahner, David; et al.
Abstract: Aims: Studies suggest that metformin is associated with reduced COVID-19 severity in individuals with diabetes compared to other antihyperglycemics. We assessed if metformin is associated with reduced incidence of severe COVID-19 for patients with prediabetes or polycystic ovary syndrome (PCOS), common diseases that increase the risk of severe COVID-19. Methods: This observational, retrospective study utilized EHR data from 52 hospitals for COVID-19 patients with PCOS or prediabetes treated with metformin or levothyroxine/ondansetron (controls). After balancing via inverse probability score weighting, associations with COVID-19 severity were assessed by logistic regression. Results: In the prediabetes cohort, when compared to levothyroxine, metformin was associated with a significantly lower incidence of COVID-19 with "mild-ED" or worse (OR [95% CI]: 0.636, [0.455–0.888]) and "moderate" or worse severity (0.493 [0.339–0.718]). Compared to ondansetron, metformin was associated with lower incidence of "mild-ED" or worse severity (0.039 [0.026–0.057]), "moderate" or worse (0.045 [0.03–0.069]), "severe" or worse (0.183 [0.077–0.431]), and "mortality/hospice" (0.223 [0.071–0.694]). For PCOS, metformin showed no significant differences in severity compared to levothyroxine, but was associated with a significantly lower incidence of "mild-ED" or worse (0.101 [0.061–0.166]), and "moderate" or worse (0.094 [0.049–0.18]) COVID-19 outcome compared to ondansetron. Conclusions: Metformin use is associated with less severe COVID-19 in patients with prediabetes or PCOS.